Efficacy of bilateral thoracoscopic sympathectomy in a patient with catecholaminergic polymorphic ventricular tachycardia. Issue 1 (30th August 2015) - Okajima, Katsunori; Kiuchi, Kunihiko; Yokoi, Kiminobu; Teranishi, Jin; Aoki, Kosuke; Shimane, Akira; Nakamura, Yoshihide; Kimura, Motoko; Horikawa, Yoshio; Yoshida, Masato; Maniwa, Yoshimasa
Abstract: A 27‐year‐old woman with frequent implantable cardioverter defibrillator (ICD) shocks related to catecholaminergic polymorphic ventricular tachycardia (VT) experienced aborted sudden death due to incessant polymorphic VT despite the administration of beta‐blockers, verapamil, and flecainide. Catheter ablation failed to suppress the polymorphic VT. Based on the temporary efficacy of the local anesthetic administered at the left and right cervical sympathetic nerves to suppress VT under an isoproterenol infusion, stepwise, bilateral thoracoscopic sympathectomy was performed. Postoperatively, no further VT or syncopal episodes were documented under ICD telemetry. Bilateral thoracoscopic sympathectomy may be an alternative for patients with drug‐refractory catecholaminergic polymorphic VT.